MANUAL THERAPY AND OSTEOPATHY - COMPARATIVE ANALYSIS - Yani Shivachev; Paraskeva Mancheva (Peytchinski Publishing, 2022)
Purpose: to study and analyze the commonalities and differences between manual therapy and osteopathy. Material and methods: a content analysis of bibliographic descriptions and relevant articles on manual techniques and their application in patients with acute and chronic problems; historical method for studying the world practices in manual therapy and osteopathy; a documentary method for the legal regulation of the considered problem is studied in the normative acts, strategic and ethical documents. Results: a review of the literature and regulations reveals the commonalities between OP and MT: both use manual techniques for spinal dysfunction to reduce pain and improve movement in the affected joints but are not recognized as independent professions. The available differences relate mainly to the lack of a legal framework for training and practice in osteopathy and legal regulation of manual therapy as a specific field in the specialty "Physical and Rehabilitation Medicine". Conclusion: The retrospective analysis clearly shows the place and role of manual therapy and osteopathy in the world. Despite the shared roots between MT and OP in Bulgaria, we find many differences in the legislative framework, training and practice. There is still no procedure for separating manual medicine into an independent medical profession in Bulgaria.